Post-secondary students’ views on health: Support for individual and social health determinants - Shyleyko, Robert; Godley, Jenny (Alberta Journal of Educational Research, 2013)
This paper examines how post-secondary students understand health, and whether opinions about health are correlated with area of study. We present results from an online survey administered in 2011 to 287 students at one post-secondary institution in Western Canada. Overall, the survey students are more likely to adopt an individualistic, rather than a social, view of health determinants. Several demographic variables, including sex and political affiliation are associated with adopting a more individualistic view of health. However, students in the Health Sciences are significantly more likely to support the social determinants of health perspective. These results suggest that medical and health science educators at this post-secondary institution may be heeding the century-old call to address social structural causes of health inequalities in their curricula. Cet article examine les perspectives d’étudiants postsecondaires sur la santé et la mesure dans laquelle celles-ci correspondent à leur domaine d’études. Nous présentons les résultats d’une enquête enligne administrée en 2011 à 287 étudiants d’une institution postsecondaire dans l’Ouest canadien. Globalement, les étudiants ayant participé à l’enquête sont plus portés à adopter une vision individualiste, plutôt que sociale, des déterminants de la santé. Il existe un lien entre plusieurs autres variables démographiques, y compris le sexe et l’affiliation politique, et l’adoption d’une perspective plus individualiste de la santé. Toutefois, les étudiants en sciences de la santé sont beaucoup plus enclins à appuyer une vision de la santé qui tient compte des déterminants sociaux de la santé. Ces résultats portent à croire que les professeurs des sciences médicales et de la santé à cette institution postsecondaire répondent à l’appel centenaire de traiter des causes sociales et structurelles des inégalités en matière de santé dans leurs cours.